EVALUATION OF THE ULTRASONOGRAPHIC SCALE IN THYROID CANCER RISK STRATIFICATION - Kolomiytsev, V.I.; Marina, V.N.; Lukavetskiy, O.V.; Dovgan, Yu.P. (World of Medicine and Biology, 2018)
The purpose of the study was to compare the main known ultrasonographic (USG) scales (TIRADS by Russ, ACR-TIRADS, ATA recommendation and U classification) in predicting of thyroid cancer. A retrospective analysis of patients’ cards for 2015-2016 has been carried out, which have undergone an operating treatment for thyroid nodules. There was a significant difference in the prevalence of thyroid cancer among patients with cystic and solid nodes, which was 4.4% and 15.1% respectively (χ2=21.082; p